INFORMATION LITERACY LEVEL OF STATE UNIVERSITY OF MALANG STUDENTS PARTICIPANT IN NATIONAL STUDENTS SCIENTIFIC WEEK 2018-2019 - Indriyani, Mutia; Safii, Moh.; Pratiwi, Yuni (BACA: Jurnal Dokumentasi dan Informasi, 2021)
This study aimed to describe the level of literacy information of State University of Malang students participants in PIMNAS 2018 and 2019 based on six standards of literacy information. This research used descriptive research method with a quantitative approach. The results showed that the information literacy level of the State University of Malang students who participated in the PIMNAS 2018 and 2019 based on six sub-variables, there are average score of identifying information needs was 3.43; average score of information-searching behavior and information sources was 3.15; average score of information search techniques and strategies was 2.96; average score of information organization and evaluation was 3.19; average score of information use and related issues was 3.14; and average score of information sharing and knowledge creation was 3.76. The author argue that the State University of Malang Library should be involved in improving student literacy in the category of using techniques and information search strategies.